PENGGUNAAN MACROMEDIA FLASH PADA MATERI LARUTAN PENYANGGA TERHADAP HASIL BELAJAR SISWA KELAS XI MAN DARUSSALAM - Teuku Badlisyah; Munira Maghfirah (Lantanida Journal, 2017)
In some cases, students face some difficulties to understand the topic of chemistry that delivered by teachers. Currently, there is no proper media that can be applied on learning process in order to enhance students’ capabilities in gaining the goal. Therefore, the study is conducted in using macromedia flash to describe buffer solution topic at Class XI Islamic Senior High School (MAN) Darussalam. This study aims to determine students' learning outcomes through the use of macromedia flash on buffer solution at class XI MAN Darussalam. The research question: is macromedia flash can be used on buffer solution material to improve student learning result of class XI MAN Darussalam?. The population of this study was the students of the second year of MAN 1 Darussalam. Meanwhile, the sample was taken from two classes; XI IPA 1 as experimental class and XI IPA 2 as control class. The sample was taken by using purposive sampling technique. The research adopted quantitative approach in using numeric data which is analyzed by statistical method. Data was collected by using multiple choice instruments. The results showed that the average score of the experimental class =79.7 and the average score of the control class = 67.5. Furthermore, the test results are analyzed by processing hypothesis test (t-test) at α = 0,95 with degrees of freedom (dk) 60, obtained tcount = 3.67 and for ttable obtained 1.67. Which is tcount ≥ t table, then H0 rejected Ha accepted. It short, the result shows the improvement of students’ learning outcome between experimental class and control class after applying macromedia flash on buffer solution material at MAN Darussalam Aceh Besar.